Multiple-Input Single-Output Ghost Imaging - Le Wang; Shengmei Zhao (IEEE Photonics Journal, 2020)
In this paper, we propose a multiple-input single-output ghost imaging scheme, named MISO-GI. In the scheme, K spatiotemporal speckle pattern sources (multiple input) simultaneously generate K different spatiotemporal modulated speckle patterns which then are illuminated on an unknown object at the same time. Then, a non-spatial-resolution bucket detector (single output) is used to detect the light field interacting with the object. According to the orthogonality of speckle patterns from different spatiotemporal speckle pattern sources, the detection signal is separated into K components corresponding to K spatiotemporal modulated speckle patterns. With the effective recovery algorithm, an image is reconstructed by using all spatiotemporal modulated speckle patterns and their corresponding components of detection signals. Both experimental and simulation results verify the feasibility of the proposed MISO-GI scheme. Moreover, the results also show that the proposed MISO-GI scheme could reduce the total sampling time by K times and improve the imaging quality comparing to traditional GI, without the decrease of the number of speckle patterns and the picture time as well as the consumption of other light field dimensions. It provides a promising avenue to realize GI with limited sampling time and has potential for more applications.